Diagnostic Challenges of Pneumocystis Pneumonia during the COVID-19 Pandemic: A Case of a Young Patient with Ground Glass Opacities and Pulmonary Embolism on Chest CT - William Lim; Maham Suhail; Keith Diaz (Case Reports in Infectious Diseases)
The coronavirus disease 2019 (COVID-19) pandemic is wreaking havoc across the globe. This pandemic has given rise to a mindset where physicians tend to neglect other causes of pneumonia, especially if the patient presents with signs and symptoms commonly associated with COVID-19. Herein, we report a case of a young man presenting to the emergency department with common clinical, radiological, and laboratory features of COVID-19 pneumonia such as shortness of breath, hypoxia, pulmonary embolism, elevated D-dimer, and bilateral ground glass opacities on computed tomography of the chest but was later diagnosed with Pneumocystis pneumonia that was treated with appropriate antibiotics and corticosteroids. This case highlights the importance of performing a thorough clinical history and differentiating the clinical and radiological features of COVID-19 pneumonia from pneumonia of other etiologies.